Effect of the Factor V Leiden Mutation on the Clinical Expression of Severe Hemophilia A - Lee, D.H.; Walker, I.R.; Teitel, J.; Poon, M.-C.; Ritchie, B.; Akabutu, J.; Sinclair, G. D.; Pai, M.; Wu, J. W. Y.; Reddy, S.; Carter, C.; Growe, G.; Lillicrap, D.; Lam, M.; Blajchman, M. A. (Thrombosis and Haemostasis, 2000)
To determine whether the factor V Leiden mutation is associated with decreased bleeding in individuals with severe hemophilia A, factor concentrate utilization, maximum annual number of bleeding episodes, and the prevalence of hemophilic arthropathy between carriers and non-carriers of the factor V Leiden mutation were compared. Heterozygosity for the factor V Leiden mutation was found in 6 of 137 subjects (4.4%). Carriers of the factor V Leiden mutation utilized less factor concentrate (geometric mean: 310 vs. 1185 units/kg/year) and had fewer bleeding episodes than non-carriers (proportion with 10 or fewer bleeding episodes in their worst year: 50 vs. 11%). However, the factor V Leiden mutation was not associated with the absence of arthropathy. The intron 22 inversion mutation of the factor VIII gene was tested for in a subgroup of 80 subjects, but it was not found to be a significant variable for any of the bleeding endpoints. The results of this small study are consistent with the hypothesis that the factor V Leiden mutation imparts a protective effect; however, a larger confirmatory study in which the factor VIII molecular defects can be controlled for is needed. Furthermore, most severe hemophiliacs who used fewer than 200 units/kg/year of factor concentrate or who had experienced 10 or fewer bleeding episodes per year did not carry the factor V Leiden mutation, suggesting that the proportion of severe hemophiliacs whose mild clinical course can be attributed to the factor V Leiden mutation is small.
Keywords: Factor V Leiden; hemophilia A; bleeding